(untitled) (Journal of Academic Research, 2025)
Carpal tunnel syndrome (CTS) is the most common upper extremity nerve compression syndrome Which affect the median nerve. Patients with CTS experience reduced sensation, dexterity, and function. Irreversible changes in nerve structure and function due to demyelination and axonal damage can occur in long-standing case.